Students’ unrest suggested measures for building peaceful learning environment in public secondary schools in Oyo State (2017)
This paper investigated the causes and consequences of students’ unrest in public secondary schools in Oyo State: as well as a measures that need to be put in place for building a peaceful learning environment. Three research questions were answered in the study. The study employed mixed method research type. A multi stage sampling technique was used to select the respondents. Students’ Unrest and Safe Learning Environment Interview Schedule (r = 0.76) was used to obtain data. Data collected were analysed using thematic approach for qualitative area. Stakeholders’ accounts revealed factors responsible for student unrest such as un-conducive learning environment, high rate of indiscipline and poor parenting among others. While the most identified effect of students unrest is poor academic achievement, increase in social vices, and vandalization of government properties. It can therefore be concluded from the findings, that stakeholders in education should provide access to good and quality education in terms of human and material resources, good and adequate means of communication to the public on government programmes, prompt payment of teachers salary and other incentives to ensure a safe learning environment and better academic performance of the students.